Diet modulates metabolic and hepatic responses to chronic pesticide mixture exposure in mice - C. Rives; N. Poirier-Jaouen; Y. Malaisé; C. M. P. Martin; M. Huillet; S. Ellero-Simatos; P. Perrier; A. Polizzi; F. Lasserre; V. Alquier-Bacquié; C. Guyon; Y. Lippi; et al. (Archives of Toxicology, 2026)

Revisiting evolution at the rear edge - Antoine Perrier; Olivia J. Keenan; Laura F. Galloway (Trends in Ecology & Evolution, 2026)

Heterogeneous Evolutionary History Defines the Rear Edge of the North American Herb Campanula americana - Antoine Perrier; Keric S. Lamb; Laura F. Galloway (Journal of Biogeography, 2026)
Aim Warmer range limits of species distributions offer a window into the ecological and evolutionary processes associated with long‐term warming, as they often harbour relicts of refugial populations from the last glaciation. However, warm‐edge populations vary in their refugial, evolutionary, and climatic histories, complicating their use as models. Here, we characterise this variation at the warmer range limit of the North American herb Campanula americana . Location Eastern North America. Taxon Campanula americana . Methods We evaluated the warmer range limit using species distribution model hindcasting, range‐wide analyses of population structure, effective migration, and phylogenetic relationships. Results Warm‐edge populations vary in their refugial history; most are relicts of historic refugial populations (i.e., rear edge), but some result from southward postglacial colonisation. Within the rear edge, populations exhibit pronounced genetic structure, forming highly isolated clusters despite contiguous geography and only modest landscape barriers. Distinct rear‐edge clusters varied in climate history and gene flow among populations, with more southern populations experiencing greater habitat decline, fragmentation and isolation. Finally, only rear‐edge populations from northern refugial areas contributed to postglacial range expansion. Main Conclusions Our study highlights the challenges of using warm‐edge populations as ecological and evolutionary models of response to climate change. Even in a geographically simple setting, warm‐edge populations exhibit refugial, genetic, and climatic heterogeneity. Characterising this variation is essential for accurately identifying rear‐edge populations and inferring their evolutionary history. Knowledge of the contribution of warm‐edge populations to range‐wide genetic variation is key when considering how these populations may inform studies of adaptation to future climate change.

P17-06 Advances in the Delayed-Type Hypersensitivity (DTH) assessment in Non-Human Primates: The Added Value of Multiple Readouts - M. Carrière; A. Perrier; S. Bonavaud; C. L'Huillier; N. Colliou; C. Thirion-Delalande; M. Ciurkiewicz; F. Gervais; R. Gravier; P. Ancian (Toxicology Letters, 2025)

An operational discontinuous Galerkin shallow water model for coastal flood assessment - A.G. Filippini; L. Arpaia; V. Perrier; R. Pedreros; P. Bonneton; D. Lannes; F. Marche; S. De Brye; S. Delmas; S. Lecacheux; F. Boulahya; M. Ricchiuto (Ocean Modelling, 2024)

Variability in grain cadmium concentration among durum wheat cultivars: impact of aboveground biomass partitioning - F. Perrier; B. Yan; F. Candaudap; O. S Pokrovsky; E. Gourdain; B. Meleard; S. Bussière; C. Coriou; T. Robert; C. Nguyen; J. Y. Cornu (Plant and Soil, 2016)

Influence of the Calcaneus Shape on the Risk of Posterior Heel Ulcer Using 3D Patient-Specific Biomechanical Modeling - V. Luboz; A. Perrier; M. Bucki; B. Diot; F. Cannard; N. Vuillerme; Y. Payan (Annals of Biomedical Engineering, 2015)

Radon Emanation in Partially Saturated Porous Media - P. M. Adler; F. Perrier (Transport in Porous Media, 2009)

Relationships between Ni-hyperaccumulation and mycorrhizal status of different endemic plant species from New Caledonian ultramafic soils - H. Amir; N. Perrier; F. Rigault; T. Jaffré (Plant and Soil, 2007)

Long-term climate change and surface versus underground temperature measurements in Paris - F. Perrier; J.-L. Le Mouël; J.-P. Poirier; M. G. Shnirman (International Journal of Climatology, 2005)

Somaclonal variation rate evolution in plant tissue culture: Contribution to understanding through a statistical approach - F. X. Côte; C. Teisson; X. Perrier (In Vitro Cellular & Developmental Biology - Plant, 2001)

Molecular diversity in pineapple assessed by RFLP markers - M. F. Duval; J. L. Noyer; X. Perrier; Coppens d’Eeckenbrugge; P. Hamon (Theoretical and Applied Genetics, 2001)